2020
DOI: 10.17977/jptpp.v5i4.13351
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Exercise for 10 Year Old Beginner Tennis Players

Abstract: <strong>Abstract:</strong> There are many forms of training to improve the quality of physical condition of the tennis court athletes, one of which is coordination training. Thus, the author would like to try applying various forms of coordination exercises that are applied to children aged 10-11 years who participate in tennis clubs in the City of Tasikmalaya to support hand coordination. The aim of this research is to find out eye-hand coordination in elementary school students. The focus of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Children who use gadgets generally focus on only staring at one object for a long time. Position less body good moment using gadgets, poor intensity lighting good so will impact badly to health eye (Mulya & Agustryani, 2020) Based on studies Preliminary at SD Inpres 25, a few students use cell phones for necessary work Duty and are already used to watching, and even some play online games. According to the teacher, even the parents of students reported that their son had time-sick eyes due to staring at a gadget screen too long.…”
Section: Problems and Question Formulationmentioning
confidence: 99%
“…Children who use gadgets generally focus on only staring at one object for a long time. Position less body good moment using gadgets, poor intensity lighting good so will impact badly to health eye (Mulya & Agustryani, 2020) Based on studies Preliminary at SD Inpres 25, a few students use cell phones for necessary work Duty and are already used to watching, and even some play online games. According to the teacher, even the parents of students reported that their son had time-sick eyes due to staring at a gadget screen too long.…”
Section: Problems and Question Formulationmentioning
confidence: 99%